2022
DOI: 10.1021/acsomega.2c05499
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of a Regenerated Cellulose Film Using Low-Pressure Plasma Treatment with Various Reactive Gases

Abstract: There is a growing interest in the fabrication of membranes and packaging materials from natural resources for a sustainable society. A regenerated cellulose (RC) film composed solely of cellulose has outstanding advantages including biodegradability, transparency, mechanical strength, and thermal stability. To expand the application of the RC film, various surface modification methods have been proposed. However, conventional chemical methods have disadvantages such as environmental burden and difficulty in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The increase in O/C during extended plasma treatment is attributed to a higher proportion of carbon with a single oxygen bond, C3, along with a reduction in the quantity of carbon bonded to fluorine, C7. It is worth noting that the degradation of fluorine-containing bonds due to plasma exposure has been reported in other papers, as in [51].…”
Section: Treatmentmentioning
confidence: 55%
“…The increase in O/C during extended plasma treatment is attributed to a higher proportion of carbon with a single oxygen bond, C3, along with a reduction in the quantity of carbon bonded to fluorine, C7. It is worth noting that the degradation of fluorine-containing bonds due to plasma exposure has been reported in other papers, as in [51].…”
Section: Treatmentmentioning
confidence: 55%
“…Extensive desorption of water may explain some non-expected results, for example, the highly hydrophilic surface finish obtained after prolonged treatment with CF 4 plasma. Namely, Kawano et al [ 26 ] reported optimal hydrophobicity (WCA 120°) after treating a cellulose film for a minute, but the WCA dropped to as low as 25° after treating the same material for 4 min.…”
Section: Discussionmentioning
confidence: 99%
“…Kawano et al [ 26 ] also utilized CF 4 plasma to coat cellulose with a thin film of fluorinated carbon. They used regenerated cellulose to synthesize thin films.…”
Section: Cellulose Hydrophobization By Gaseous Plasma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation into the effects of plasma treatment on different types of the membranes such as polyacrylonitrile 23 , cellulose nitrate 24 , polyethersulfone 25 , polyacrylonitrile copolymer 26 , polysulfone 27 , polypropylene 28 , regenerated cellulose 29 , cellulose acetate composite polyion complex 30 , polycarbonate 31 , Aromatic Polyamide 32 , polytetrafluoroethylene 33 has been reported by different researchers. The study reveals the distinct surface modifications as a result of the incorporation of functional groups into the plasma-treated membrane, which alter the antifouling and permeability properties of the membrane.…”
Section: Introductionmentioning
confidence: 99%